2013
DOI: 10.1016/j.intimp.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

B cell activating factor-dependent expression of vascular endothelial growth factor in MH7A human synoviocytes stimulated with tumor necrosis factor-α

Abstract: Angiogenesis in rheumatoid arthritis (RA) is one of the histological hallmarks, which is mediated by expression of vascular endothelial growth factor (VEGF) in RA synovium. VEGF expression is enhanced by TNF-α, the main pro-inflammatory cytokine in RA. B cell activating factor (BAFF) which plays a role in maturation and maintenance of B cells is also associated with autoimmune RA. Here, we investigated whether BAFF could regulate VEGF expression in TNF-α-stimulated synovium using MH7A synovial cells that are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…As HIF-1 α is associated with the pathogenesis of RA 8, 9 and BAFF controls RA angiogenesis, 31 we investigated whether BAFF expression is regulated by HIF-1 α in FLS. We examined hBAFF and HIF-1 α expression levels under normoxic conditions, and MH7A cells were treated with various concentrations of TNF- α for different times (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As HIF-1 α is associated with the pathogenesis of RA 8, 9 and BAFF controls RA angiogenesis, 31 we investigated whether BAFF expression is regulated by HIF-1 α in FLS. We examined hBAFF and HIF-1 α expression levels under normoxic conditions, and MH7A cells were treated with various concentrations of TNF- α for different times (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…27, 29, 30 We reported previously that TNF- α -induced BAFF controls RA angiogenesis by regulating vascular endothelial growth factor (VEGF) expression in synoviocytes. 31 …”
mentioning
confidence: 99%
“…It has been confirmed that RA-FLS stimulated by IFN-c or TNF-a can induce significant increases in the BAFF mRNA and protein levels [14]. Lee GH and his colleagues showed that the upregulated expression of BAFF could be coupled with VEGF-mediated angiogenesis in FLS [15].…”
Section: Fls Interacts With B and T Cellsmentioning
confidence: 89%
“…In contrast, it is upregulated in activated T cells and activated or malignant B cells [13]. The expression of BAFF is upregulated by multiple cytokines, including TNF-a, IFN-c, and TGF-b as well as estrogen [14,15].…”
Section: Biological Functions Of Baff and Its Familymentioning
confidence: 99%
“…FLS thus enhance immune responses to antigens generated by continual degradation of articular cartilage. Much evidence suggests that FLS promote angiogenesis via expression of SDF-1, fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF) [28,29]. FLS have also been suggested to participate in osteoclastogenesis, which is a pivotal mediator of bone erosion in RA.…”
Section: Discussionmentioning
confidence: 99%